The Cyclic and New Ekpyrotic Scenarios - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will study variants of the original ekpyrotic scenario, which are introduced in order to solve some problems with the original model. These are the cyclic model of Steinhardt and Turok, and the new ekpyrotic model of Buchbinder, Khoury and Ovrut.